Do Grade II Ankle Sprains Have Chronic Effects on the Functional Ability of Ballet Dancers Performing Single-Leg Flat-Foot Stance? An Observational Cross-Sectional Study - Bruno Dino Bodini; Giacomo Lucenteforte; Pietro Serafin; Lorenzo Barone; Jacopo A. Vitale; Antonio Serafin; Valerio Sansone; Francesco Negrini (Applied Sciences, 2019)
Ballet dancers have a higher risk than the general population of ankle sprains. Ankle proprioception is of the utmost importance for executing static and dynamic positions typical of ballet dancing. Ankle sprains can create changes in functional ability that may affect ballet performance. The aim of this cross-sectional observational study is to evaluate if non-professional ballet dancers that were previously injured with a grade II ankle sprain carry a long-term stability deficit in ballet specific positions (passé, arabesque) and in single-leg flat-foot stance, thereby affecting ballet performance. We enrolled 22 amateur female ballet dancers, 11 who previously had a grade II ankle injury and 11 who had no history of ankle injury. Stabilometric data (Center of Pressure Speed and Elipse Area) were assessed with the postural electronic multisensory baropodometer in normal, arabesque, and passè positions with both open and closed eyes. Using an unpaired t-test, we compared healthy and pathological feet of the ankle injury group for a standard monopodalic position and two ballet-specific positions. No difference between pathological and healthy feet of non-professional ballet dancers who suffered grade II ankle injury was detected. According to the parameters considered in this study, grade II ankle sprains seem to have a favorable prognosis in the sample that we evaluated.